Supplement to Frege’s Theorem and Foundations for Arithmetic
Derivation of the Principle of Extensionality from Basic Law V
[Note: We use ϵF to denote the extension of the concept F.]
Assume Extension(x) and Extension(y). Then ∃F(x=ϵF) and ∃G(y=ϵG). Let P,Q be arbitrary such concepts; i.e., suppose x=ϵP and y=ϵQ.
Now to complete the proof, assume ∀z(z∈x≡z∈y). It then follows that ∀z(z∈ϵP≡z∈ϵQ). So, by the Law of Extensions and the principles of predicate logic, we may convert both conditions in the universalized biconditional to establish that ∀z(Pz≡Qz). So by Basic Law V, ϵP=ϵQ. So x=y.